Digital Adab Education in Early Childhood from an Islamic Education Perspective: A Case Study of RA Al-Islamiyyah Kemayoran, Jakarta - Rochmi Hastuti; Asri Andriana Lituhayu (Amorti: Jurnal Studi Islam Interdisipliner, 2026)
The rapid development of digital technology has increased young children's exposure to gadgets, creating new challenges for character formation. From the perspective of Islamic education, the use of digital technology should be accompanied by the cultivation of adab (proper moral conduct) to ensure that children use digital media responsibly from an early age. This study aims to examine the implementation of digital adab education for early childhood from the perspective of Islamic education at RA Al Islamiyyah Kemayoran, Central Jakarta. A qualitative case study design was employed. Data were collected through interviews with the principal, teachers, and parents, supported by observations and document analysis. The data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal three main results. First, digital adab education is implemented through the habituation of Islamic values, teachers' role modelling, and guided use of digital media in learning activities. Second, successful implementation is strengthened by collaboration between the school and families through parental guidance, continuous communication, and consistent reinforcement of positive digital habits at home. Third, digital adab education contributes to the development of disciplined, responsible, respectful, and ethically aware digital behaviour among young children. This study concludes that digital adab education should focus not merely on limiting children's use of technology but on developing Islamic character through sustained collaboration between schools and families.